IDENTIFIKASI KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X IPA DITINJAU DARI INDIKATOR KEMAMPUAN BERPIKIR KRITIS DAN GENDER - Mentari Miswari; Melva Silitonga; F Fajriyah (Universitas Negeri Medan, 2020)
This study aims to determine students' critical thinking abilities in SMA Swasta Budisatrya Medan in ecosystem material. The ability to think critically is then analyzed based on indicators and compared with gender. The method used in this research is descriptive method with quantitative and qualitative approaches. The research sample is 69 students. The instrument of data collection is a test of critical thinking skills. Tests are given after students get material from the subject teacher. The technique used to process the scores obtained is to use a benchmark reference assessment technique (PAP). The results showed that students' thinking skills in ecosystem material were on average medium criteria, followed by low categories, then high and only 4 students who had critical thinking skills in the very high category. Overall, students' critical thinking skills are in the medium category. The highest critical thinking ability of students is on the indicators of strategy and tactics with moderate criteria, followed by conclusions, and provides a basic explanation. Furthermore, the lowest critical thinking ability of students is in the indicators of building basic skills and followed by making further explanations. The critical thinking ability of female students is higher than that of male students with an average score of 73 and is in the criteria of being moderate. While the average value of critical thinking skills of male students is only 64 and is in the low criteria. There is no significant difference between the critical thinking abilities of male and female students.